Community-Based Efforts to Control Infectious Diseases - Mustar Mustar; Yamtana Yamtana; Hasnidar Hasnidar; Muhammad Hilmi afthoni (Journal of Public Health Indonesian, 2025)
This study aims to analyze the effectiveness of community-based approaches in addressing infectious diseases at the local level, particularly in the city of Surakarta. This approach involves community empowerment through the engagement of local health cadres and the formation of environmental awareness groups that actively carry out disease prevention activities. The method used is a case study with data collected through interviews, observations, and documentation. The results of the study indicate that the community-based approach has successfully increased awareness and behavioral changes among the public in adopting healthy lifestyles, such as maintaining environmental cleanliness and independently conducting case tracking. Moreover, the strengthening of social capital and local leadership has proven to be crucial factors in the success of the program. Challenges encountered include low digital literacy among cadres and the general community, limiting the use of information technology. In conclusion, the community-based approach is an effective strategy to complement formal healthcare services in controlling infectious diseases. This model is recommended for replication with adjustments tailored to local socio-cultural characteristics.